2002
DOI: 10.1002/cncr.11019
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer genetics in African Americans

Abstract: Silberkugel: Eine stereoselektive Synthesemethode für polysubstituierte Tetrahydronaphthole unter [Ag+]/NPO‐Katalyse wurde entwickelt. Die Reaktionen verlaufen über eine beispiellose [4+2]‐Cyclisierung von 2‐(2‐Formylphenyl)ethanon mit einem Alken und gelingen in sowohl inter‐ als auch intramolekularer Weise. NPO=Pyridin‐N‐oxid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 39 publications
2
101
0
Order By: Relevance
“…Several studies report that the prevalence of significant mutations is similar in black and white women with a family history of breast cancer, suggesting that black and white women would be expected to benefit equally from predictive genetic testing. 38,39 The low rates of ordering genetic tests for Huntington disease among minority-serving physicians may reflect early studies suggesting a lower prevalence of Huntington disease among blacks compared with whites, although more recent data report similar prevalence rates across white and black populations. 40 -42 Although minority patients may benefit from genetic testing as much as nonminority patients, if minority patients are sicker and have more complex health needs than majority patients, these health issues may crowd out the provision of genetic services.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that the prevalence of significant mutations is similar in black and white women with a family history of breast cancer, suggesting that black and white women would be expected to benefit equally from predictive genetic testing. 38,39 The low rates of ordering genetic tests for Huntington disease among minority-serving physicians may reflect early studies suggesting a lower prevalence of Huntington disease among blacks compared with whites, although more recent data report similar prevalence rates across white and black populations. 40 -42 Although minority patients may benefit from genetic testing as much as nonminority patients, if minority patients are sicker and have more complex health needs than majority patients, these health issues may crowd out the provision of genetic services.…”
Section: Discussionmentioning
confidence: 99%
“…A number of small prevalence surveys in Black women have yielded varying results with respect to BRCA prevalence and penetrance specific to AA women Frank et al 2002;Gao et al 2000;Haffty et al 2005;John et al 2007;Kanaan et al 2003;Malone et al 2006;Mefford et al 1999;Nanda et al 2005;Olopade et al 2003;Pal et al 2004Pal et al , 2008Panguluri et al 1999;Pegoraro et al 2003;Shen et al 2000). This lack of knowledge is perpetuated by low rates of participation by AA women in clinical and research BRCA genetic counseling and testing (Armstrong et al 2005;Halbert et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic susceptibility to breast cancer has been identified in various races and ethnicities [5][6][7][8][9][10][11][12]. However, the majority of research on genetic cancer risk assessment (GCRA) for hereditary breast and ovarian cancer has been conducted in predominantly non-Latino white samples, and most ethnic minority studies focus on the prevalence of BRCA mutations and genetic testing attitudes and motivation among African American cohorts [12][13][14][15][16][17][18][19][20]. Although the few studies focused on Latinos and GCRA have found that Latinos may have low knowledge [21][22][23] and negative perceptions [24] of cancer genetic testing, others have identified positive attitudes and interest in participating in cancer genetic services and testing [23,25].…”
Section: Introductionmentioning
confidence: 99%